Book-To-Market Ratio, Dividend Yield and Price- Earnings Ratio Effects Towards Stock Return: Evidence from The Property and Real Estate Stocks in Indonesia (Journal of Business and Management, 2022)
In 2020, the pandemic has triggered a lot of new investors to invest in the stock market. Stocks are preferred as an investment because if done right, stocks can offer high returns. Several companies desired by investors are property firms, because they can offer good returns when the time is right. Moreover, property sector is one of the most growing sectors in Indonesia, with growth rate exceeding the GDP. This makes stocks of this sector interesting. Nevertheless, stock investment is a medium to high risk investment, and while it can give investors higher returns it can also give higher losses. New investors need to do analysis before putting their money on certain stocks. Therefore, the research’s objective is to analyze the relationship between financial ratios such as book-to-market ratio, dividendyield and price-earnings ratio towards property stocks returns in Indonesia from 2015-2019. Secondary data, collected from various sources are used as references. The data were analyzed using panel data regression analysis. This study reveals that the book-to-market ratio has a significant negative correlation with stock returns. Dividend yield and price-earnings ratio has negative, insignificant relationship.Keywords: book-to-market ratio, dividend yield, price-earnings ratio, stock returns, property and real estate stocks.